Presentation: Interdisciplinarity in Andean Studies - Zegarra Moretti, Carlos (2022)
Reflecting the richness and complexity of Andean studies, this issue of Allpanchis (No. 89, 2022-I) brings together different approaches to Andean history. In this way, readers can benefit from the results offered by the archaeological, linguistic, philological, cultural and historiographical analyzes presented here. Thus, the archaeologist Nils Sulca analyzes in detail the urban contribution of Wari (600 AD - 1000 AD), taking as a case study those settlements that reflect the structures and technologies of the imperial expansion of this culture.